THE INTELLECTUAL DEVELOPMENT OF THE PRODUCT-SERVICE SYSTEM CONCEPT: A CITATION / CO-CITATION ANALYSIS - Zehoul, Anne B. (Revista Latino-Americana de Inovação e Engenharia de Produção, 2021)
The concept of product-service system (PSS) can be described as a market proposition that increases the value of a product by adding additional services. The present paper aims to contribute to the current understanding of PSS research field by identifying and visualizing its theoretical evolution. A citation and co-citation bibliometric analysis was conducted and it was possible to identify that PSS theory was supported by an integrated approach of the servitization (VANDERMERWE; RADA, 1988)and the service-dominant logic concepts. A co-citation map enables the visual representation of the intellectual structure of PSS research field contributing to better identify gaps and opportunities for future research